186. Insight into Schizophrenia and Its Relationship With Clinical Symptoms: A Meta-Analysis Involving 20 515 Patients. (20th March 2017) - Gilleen, James; Strelchuk, Daniela; Palmer, Emma
Abstract: Background: Lack of insight is common in patients with schizophrenia and a large number of studies have endeavored to clarify the relationship between level of insight and degree of clinical symptomatology. This study aimed to advance our understanding of this relationship by conducting an up-to-date meta-analysis of all relevant studies published to date. Methods: A literature search identified 151 eligible studies published up to August 2016 which together included 20 515 patients with schizophrenia. The statistical associations between insight, its sub-components, and clinical symptoms were analyzed to calculate pooled effects from all studies included. Additional planned analyses included examination of whether clinical, procedural, or demographic variables moderated the strength of these relationships. Results: Results revealed significant negative associations between global insight and positive (ES = −.27), negative (ES = −.22) and global (ES = −.28), symptoms; and a significant though weaker association with depressive symptoms (ES = .20; all P < .001). In terms of individual symptoms, insight held the strongest and most negative association with Unusual Thought Content ( r  = −.46, P < .001) and disorganization ( r  = −.38, P < .001). There was substantial variation in the strength of association between individual components of insight and symptoms. Meta-regression analyses revealed that illness duration, number of psychotic episodes, age, and age of onset significantly influences the strength of the relationship between insight and symptoms. Stage of illness, assessment scale, and rater (patient vs. clinician) also moderate these relationships. Conclusion: This study supports the general notion that insight and psychopathology are significantly associated in patients with schizophrenia, however, as the magnitude of associations are generally low to medium, overall findings suggest insight is largely independent from symptomatology. Results are of relevance to both clinical practice and future research studies.